Uma experiência em design de produto em uma indústria calçadista de Nova Serrana-MG - Heloisa Nazare dos Santos (2009)
The footwear industry of Nova Serrana has as the main markets Minas Gerais and São Paulo. It shows a small insertion in the international scenery, exporting less than 5% of its production. In the domestic market, this city is recognized as the as a manufacturer of shoes popular, having low value, designated to the public of classes C and D. The small or almost null incorporation of proper design into their products is a factor that contributes significantly for a vision of the industry of copy, limiting the competitiveness of the local enterprises. In this context, this work seeks to analyze the possibilities of insertion of the design in local industry of sport shoes. It has been raised the production process and the development of products of the enterprise, while it was developed a new line of products, aiming to attend the needs of the consumer market without the utilization of the copy. From the analyses of the results of theproject, it has been discussed the obstacles for the insertion of the design in the enterprise and proposed a new method for the development of the product of the company.